2018
DOI: 10.24874/mvm.2018.44.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of an Automotive Single Plate Clutch

Abstract: This paper presents the stresses and deformations of the assembly of the automotive single plate clutch depending on the applied materials. Structural analysis of the clutch was performed by using the finite element method for a repressive vehicle example -Toyota KUN 25. First, the input data for the numerical analysis was calculated. Numerical analysis was performed in the ANSYS software package. As a result, the values of stresses and deformations that occur on the clutch during the vehicle exploitation are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Thereby we can confirm that the results of FEM are optimal. This result is similar to the results of finite element analysis and is more optimal than the results in the study [8] with a stress of 271.97MPa and [9] with a stress of 167.91MPa.…”
Section: Surface Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…Thereby we can confirm that the results of FEM are optimal. This result is similar to the results of finite element analysis and is more optimal than the results in the study [8] with a stress of 271.97MPa and [9] with a stress of 167.91MPa.…”
Section: Surface Analysissupporting
confidence: 88%
“…rivet hole diameter is 3.25mm with a stress of 66.889MPa and a strain of 0.033115mm. This result is similar to the results of finite element analysis and is more optimal than the results in the study [8] with a stress of 271.97MPa [9] with a stress of 167.91MPa. From the results of Table 8, it is shown that the error of the Taguchi method is much larger than that of the GRA method.…”
Section: Surface Analysissupporting
confidence: 88%
See 1 more Smart Citation